Nos bastidores do palácio: a Casa Civil do estado do Tocantins (1989 - 2019) - Rocha, Gisele Regina (Universidade Federal do Tocantins, 2024)
The dissertation is linked to the research line State, Society and Educational Practices of the Academic Master's Degree in Education at the Federal University of Tocantins (UFT). It depicts the implementation of the Casa Civil, whose attribution is to directly advise the Chief of the Executive Power in coordinating government actions, including those of other secretariats. It is also responsible for evaluating the legislative proposals that the Chief Executive sends to the Legislative Power and sends official government acts for publication. The dissertation reports these backstage at Palácio Araguaia in the version of civil servants who worked at the Civil House from 1989 to 1995. To carry out the research, Oral History supported it with references, such as: Verena Alberti, Sebe Meihy. In administration, Chiavenato (2014), Maximiano (2004), Nora (1993). On Tocantins, Temis Parente (1999), Otavio Silva (2008), Maria Cavalcante (2003) and Jocyléia Santos (2007). Triangulation of data, Bibliographic Research, Documentary Collection (photographs and websites) and Field Research with semi-structured interviews with scripts of questions that deal with the implementation, official acts, governors, human resources and the design of the bodies were carried out. administrative. It was concluded that the State made history in the 1990s, the Civil House in the backstage of the Palace had and has labyrinths, people's history, unofficial regulations, daily toil, memories of servants who built the public administration of the State of Tocantins.